1995
DOI: 10.1017/s0950268800052158
|View full text |Cite
|
Sign up to set email alerts
|

VerotoxinogenicCitrobacter freundiiassociated with severe gastroenteritis and cases of haemolytic uraemic syndrome in a nursery school: green butter as the infection source

Abstract: SUMMARYA summer outbreak of severe gastroenteritis followed by haemolytic uraemic syndrome (HUS) and thrombotic thrombocytopenic purpura in a nursery school and kindergarten is described. Sandwiches prepared with green butter made with contaminated parsley were the likely vehicle of infection. The parsley originated from an organic garden in which manure of pig origin was used instead of artificial fertilizers, Cornally identical VerotoxinogenicCitrobacter freundiiwere found as causative agents of HUS and gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
2
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 29 publications
(33 reference statements)
0
74
2
4
Order By: Relevance
“…Nevertheless, under unknown conditions Stx phages are able to infect EAEC strains, thus pointing to an extended host range. Previous findings about the presence of Stx phages and stx genes in Enterobacteriaceae other than E. coli also show this possibility (35,36,52).…”
Section: Discussionmentioning
confidence: 73%
“…Nevertheless, under unknown conditions Stx phages are able to infect EAEC strains, thus pointing to an extended host range. Previous findings about the presence of Stx phages and stx genes in Enterobacteriaceae other than E. coli also show this possibility (35,36,52).…”
Section: Discussionmentioning
confidence: 73%
“…However, it is important to mention the possibility of stx genes being occasionally present in members of Enterobacteriaceae other than E. coli, such as Citrobacter freundii (21) or Enterobacter cloacae (22). Even though PCR detection of stx genes does not allow one to distinguish STECs from other organisms which can occasionally carry these genes, some reports suggest they might be equally important from the clinical perspective, as they have been found to be associated with cases of gastroenteritis and hemolytic uremic syndrome (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…They found that 43% of these children had an E. coli strain other than O157:H7 in their stool: O26: H11/H-(15%), O157:H-(10%), O145: 28/H-(9%), O103/H2/H-(3%) and O111/H8/H (3%). E. coli is the most commonly involved species, Shigella Dysenteriae typeⅠ and Citrobacter freundii have less frequently observed [26] .…”
Section: Epidemiologymentioning
confidence: 99%